2008
DOI: 10.1103/physreva.78.013818
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the dispersion induced by a slow-light system based on coupled active-resonator-induced transparency

Abstract: International audienceWe demonstrate experimentally coupled active-resonator-induced transparency in a fiber system. We show that the use of Er3+-doped fibers can compensate for the optical losses leading to a high transparency of the system. Using a Mach-Zehnder fiber interferometer, we measure the dispersion properties of our coupled active resonators under different pumping rates. We show that the active feature of the system allows us to engineer the different orders of its artificial dispersion. This expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…10 We have shown that this method can be applied to characterize resonators containing amplifying system or coupled active resonator systems which are attractive for dispersion tailoring and all optical signal processing applications. 13,[30][31][32] Assuming that faster scanning of the probe wavelength can be achieved in order to measure lower Q-factors than those characterized in this paper, this technique would also be of interest to characterize integrated microresonators whose coupling characteristics are not easily tunable. 33 …”
Section: Resultsmentioning
confidence: 97%
“…10 We have shown that this method can be applied to characterize resonators containing amplifying system or coupled active resonator systems which are attractive for dispersion tailoring and all optical signal processing applications. 13,[30][31][32] Assuming that faster scanning of the probe wavelength can be achieved in order to measure lower Q-factors than those characterized in this paper, this technique would also be of interest to characterize integrated microresonators whose coupling characteristics are not easily tunable. 33 …”
Section: Resultsmentioning
confidence: 97%
“…The coupling of two resonators results in splitting of the frequency, which counteracts light absorption in one resonator and generates slow light by coupled resonator induced transparency. Dumeige [15] studied coupled resonator induced transparency in erbium-doped fibers and measured slow light signals by an interference method. Terrele [16] reported a Mach-Zehnder interferometric gyroscope based on a fiber ring coupled resonator; the sensitivity increased by 30% than measurements without slow light.…”
Section: Introductionmentioning
confidence: 99%
“…However, one established way of overcoming losses is by incorporating optical gain, creating an "active" system. [19][20][21][22][23] Features of gain enhancement have been theoretically analyzed, and experimentally studied in chains of plane-parallel Fabry-Perot resonators. 22 Recently, we have demonstrated collective modes in an amplifying linear array of spherical microdroplet resonators in non-contact mode and showed that these modes were realized by direct-coupling of the Fabry-Perot resonances of a spherical cavity.…”
mentioning
confidence: 99%